Upregulation of Nuclear Factor of Activated T-Cells by Nerve Injury Contributes to Development of Neuropathic Pain - Cai, You-Qing (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Nerve injury induces long-term changes in gene expression in the nociceptive circuitry and can lead to chronic neuropathic pain. However, the transcriptional mechanism involved in neuropathic pain is poorly understood. Nuclear factor of activated T-cells (NFATc) is a transcriptional factor regulated by the Ca(2+)-dependent protein phosphatase calcineurin. In this study, we determined nerve injury–induced changes in the expression of NFATc1–c4 in the dorsal root ganglia (DRG) and spinal cords and their role in the development of neuropathic pain. The mRNA of NFATc1–c4 was detected in the rat DRG and dorsal spinal cord. Nerve injury transiently elevated NFATc1–c3 mRNA levels and persistently increased NFATc4 and C-C chemokine receptor type 2 (CCR2) mRNA levels in the DRG. However, NFATc1–c4 mRNA levels in the spinal cord were not altered significantly by nerve injury. Nerve injury also significantly increased the protein level of dephosphorylated NFATc4 in the DRG. Intrathecal injection of the specific NFATc inhibitor 11R-VIVIT or the calcineurin inhibitor FK-506 (tacrolimus) early after nerve injury significantly attenuated the development of tactile allodynia. In addition, treatment with FK-506 or 11R-VIVIT significantly reduced the mRNA levels of NFATc4 and CCR2 but not large-conductance Ca(2+)-activated K(+) channels, in the DRG after nerve injury. Our findings suggest that peripheral nerve injury causes a time-dependent change in NFATc1–c4 expression in the DRG. Calcineurin-NFATc–mediated expression of pronociceptive cytokines contributes to the transition from acute to chronic pain after nerve injury.